Perancangan Media Pembelajaran Interaktif Bahasa Isyarat Mengenal Huruf Dan Angka Bagi Siswa Penyandang Disabilitas Tunarungu Berbasis Andorid - Juni Amanullah; Lukman Santoso (STEKOM PRESS, 2022)
In the current era, learning adheres to the 2013 curriculum which includes HOTS (Higher Order Thinking Skills) consisting of critical thinking competencies, creativity and innovation, communication skills, collaboration skills and selfconfidence. These five things need to be trained or improved for deaf children so that they can take part in learning well. So learning media products are made that can be used to recognize letters and numbers. This Learning Media is equipped with sign language to support the understanding of deaf children in addition, it is packaged with an attractive appearance so that deaf children are interested in learning it. Often in daily teaching and learning activities students still often experience problems in remembering the material being taught both in the introduction of letters and also the introduction of numbers and what becomes an obstacle for students learning must be done repeatedly so that they can remember it and can really understand what it means. being taught and also they are sometimes bored and lazy in learning. From the problems that occur above, it is necessary to have a learning media that can help children with disabilities, especially the deaf, especially for the introduction of numbers and letters so that they can easily understand and understand letters and numbers. not bored, bored and lazy in learning. Learning media in the form of an android application so that it can be used on smartphones which are currently very widely used by both teachers and parents of students with disabilities.